Transitional cell carcinoma of the ureter and struvite calculi - Freitas, Danielo Garcia de; Garcia, Adriano Scaff; Freitas Filho, Osvaldo de (São Paulo Medical Journal, 1999)
CONTEXT: The association of primary carcinoma of the ureter and lithiasis is extremely rare. We report a rare case of a primary carcinoma of the ureter with corariform calculus. CASE REPORT: 60-year-old phaeodermal female, reported a history of right-side nephritic colic, hyperthermia and pyuria during the past 20 years and had received treatment for urinary infections a number of times. The first clinical presentation was related to lithiasis and the tumor had not been shown up by excretory urography, cystoscopy or ultrasonography. Two months after the calculus had been eliminated, the patient began to have serious symptoms and a grade III transitional cell carcinoma of the ureter was discovered. Total nephroureterectomy and M.V.A.C. (Metotrexate + Vinblastina + Doxo Rubicina + Cisplatina) chemotherapy were tried unsuccessfully. In this report we emphasize the diagnostic difficulty caused by the concomitant presence of the two pathologies. In our opinion, the rapid evolution in this case is directly related to the high grade of the tumor.